Fractionation and valorization of industrial bark residues by autohydrolysis and enzymatic saccharification. (September 2020) - Neiva, Duarte M.; Costa, Ricardo A.; Gominho, Jorge; Ferreira-Dias, Suzana; Pereira, Helena
Abstract: Eucalyptus globulus (Eg) and Picea abies (Pa) residual barks from pulp and solid wood industries were studied regarding their fractionation. Extractive-free barks were treated through autohydrolysis (severity factors 3.3–4.7) to obtain non-cellulosic rich oligosaccharides/monosaccharides moieties, followed by enzymatic saccharification of the (mostly unaltered) lignin/cellulose enriched residues. The maximum sugar yields obtained from autohydrolysis were 11 and 14 g/100 g extractive-free bark for Eg and Pa with typical fermentation inhibitors reaching 8 g/100 g. Two commercial enzymes (Saczyme Yield and Ultimase BWL40) were tested to extractive-free bark and residues from autohydrolysis. Ultimase allowed 73% and 51% global sugar yield for Eg and Pa, respectively, while Saczyme showed poorer results especially when applied to Pa. The solids obtained after saccharification were highly enriched in lignin. Autohydrolysis followed by enzymatic saccharification enabled bark fractionation into streams rich in xylooligosaccharides or arabinooligosaccharides (hemicellulosic polymers), glucose from cellulose and lignin remaining in the solid residue. Graphical abstract: Unlabelled Image Highlights: E. globulus and P. abies barks are important upgradable industrial residues. Bark autohydrolysis can be tuned towards xylo/arabinooligosaccharides production. Autohydrolysis enhances bark enzymatic hydrolysis monosaccharides up to 98% yields. Autohydrolysis and enzymes efficiently fractionate the lignocellulosic bark matrix.